Formação dos primeiros graduandos do Curso de Licenciatura em Educação do Campo - UFT Arraias/TO: um estudo do currículo prescrito e vivenciado - Rodrigues, Joélia dos Santos (Universidade Federal do Tocantins, 2020)
The present work has as its theme the formation of teachers, having as a reference point the proposal to study the curriculum of the Course in Education in the Field of Codes and Languages - Visual Arts and Music, from the Federal University of Tocantins - Campus de Arraias, implemented in 2014, specifically in aspects related to the Visual Arts and Music qualifications and about the challenges faced by the teachers and students of that course, based on the training process of the first graduates. The general objective of the study was to carry out observations and document analysis in order to understand the challenges faced by teachers and students during the training process, aiming at contributions to the curriculum. The curriculum of the course is organized through three distinct and interrelated groups, contemplating moments of common study, moments of specific study and free moments of deepening of knowledge, proposing an interdisciplinary knowledge, based on two dimensions of integrated training alternation: university time and community time, with qualifications in two areas of knowledge - Visual Arts and Music. The work was based on theorists such as: (SACRÍSTAN, 2000); (SANTOMÉ, 1998); (PEREIRA and SILVA, 2017); (FERNANDES, PACHECO and OLIVEIRA, 2013), (QUEIROZ and MARINHO, 2005), (CARVALHO, 2016) among others. This study points out the need to organize the curricular structure and to reflect on the workload for the Visual Arts and Music subjects of the course, thus contributing to rethink the training that future professionals in this area are having, and the possible practices of teaching-learning for training appropriate to the reality found in school institutions.